Effects of aging on chlorinated plasma polymers - Turri, Rafael Gustavo [UNESP]; Amorim, Milena Kowalczuk Manosso [UNESP]; Hadich, Tayan Vieira [UNESP]; Fernandes, Isabela Cristina [UNESP]; Fernandes, Gabriel Ferreira [UNESP]; Rossi, Diego [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Durrant, Steven Frederick [UNESP] (FapUNIFESP (SciELO), 2017)
Thin films deposited from propanol-chloroform-argon mixtures by plasma enhanced chemical vapor deposition at different partial pressures of chloroform in the feed, CCl, were characterized after two years of aging and their characteristics compared with their as-deposited properties. Film thickness decreased and surface roughness increased with aging. Surface contact angles also increased with aging for the chlorinated films. For the film deposited with 40% chloroform in the feed the contact angle increased about 14°. Transmission infrared and Energy dispersive X-ray spectroscopy revealed that the films gain carbonyl and hydroxyl groups and lose chlorine and hydrogen on aging. Chlorination appears to make the films more durable. Delamination was observed for the unchlorinated films.
Keywords: A-C:H:O:Cl; Contact angle; IRS; Stability; Thin films